Strengthening Entrepreneurial Management Competence through Industrial Visits to Beryl's Chocolate & Confectionery, Malaysia - Fadhil, Rahmat; Halim, Hendra; Ramadhani, Evi; Agustina, Raida; Dinaroe, Dinaroe; Rahimi, Sayyid Afdhal El; Erlidawati, Erlidawati; Lufika, Raihan Dara (Universitas Syiah Kuala, 2025)
The industrial visit to Beryl's Chocolate Confectionery Sdn Bhd in Malaysia aimed to strengthen the competencies of lecturers and student entrepreneurship advisors at Syiah Kuala University in the areas of global business strategy, technological innovation, and business sustainability. The primary challenge addressed was the need for enhanced understanding and application of entrepreneurial principles to support student entrepreneurship programs, aligning with SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 12 (Responsible Consumption and Production). Utilizing the service learning method, this community service activity involved experiential learning through direct observation and engagement with industry best practices. The results demonstrated a significant improvement in participants knowledge and understanding, with an average increase of 22.67% between pre-test and post-test scores. Participants gained practical insights into production processes, digital marketing strategies, and sustainability principles that could be applied to local entrepreneurial contexts. The collaborative involvement of various stakeholdersuniversity departments, industry partners, and travel service providersensured the activity's success and served as a model for future initiatives. This program not only addressed existing knowledge gaps but also opened avenues for integrating global business practices into local entrepreneurship development, contributing to the broader goals of sustainable economic growth and education quality improvement.